Air pressure propagation through Wind Cave and Jewel Cave: How do pressure waves travel through barometric caves? - Annika Gomell; Daniel Austin; Marc Ohms; Andreas Pflitsch (International Journal of Speleology, 2021)
In barometric caves, air pressure gradients between the outside atmosphere and the cave induce strong bidirectional compensating currents, which control almost all elements of speleoclimatology, including air temperature, humidity, and CO2 dynamics. Therefore, this study set out to investigate air pressure propagation through Wind Cave and Jewel Cave – two major barometric cave systems in the Black Hills of South Dakota, USA. Based on high-resolution air pressure data from both the surface and several measurement sites inside the caves, four systematic changes of pressure waves during their journey through the caves and their related speleoclimatological processes were identified and discussed: Compared to the outside atmosphere, the pressure signals within Wind Cave and Jewel Cave showed (1) an absolute displacement due to different altitudes of the measuring sites, (2) a delay related to the travel times of the pressure wave to the measuring sites, (3) a smoothing effect, and (4) a damping effect due to long response times of the caves to external pressure changes. The spatial distribution of the changes observed in this study shows that for Wind Cave, the cave opening and the narrow entrance area represent the main obstacle for pressure propagation, while for Jewel Cave, the deep areas have the greatest influence on the development of air pressure gradients. Our analyses provide completely new insights into the processes and mechanisms inside barometric caves, which will significantly contribute to the understanding of pressure-related airflow dynamics and all related elements of speleoclimatology.